Zinc pyrithione is a potent inhibitor of PLPro and cathepsin L enzymes with ex vivo inhibition of SARS-CoV-2 entry and replication - Jerneja Kladnik; Ana Dolinar; Jakob Kljun; David Perea; Judith Grau-Expósito; Meritxell Genescà; Marko Novinec; Maria J. Buzon; Iztok Turel (Journal of Enzyme Inhibition and Medicinal Chemistry)
Zinc pyrithione (1a), together with its analogues 1b–h and ruthenium pyrithione complex 2a, were synthesised and evaluated for the stability in biologically relevant media and anti-SARS-CoV-2 activity. Zinc pyrithione revealed potent in vitro inhibition of cathepsin L (IC50=1.88 ± 0.49 µM) and PLPro (IC50=0.50 ± 0.07 µM), enzymes involved in SARS-CoV-2 entry and replication, respectively, as well as antiviral entry and replication properties in an ex vivo system derived from primary human lung tissue. Zinc complexes 1b–h expressed comparable in vitro inhibition. On the contrary, ruthenium complex 2a and the ligand pyrithione a itself expressed poor inhibition in mentioned assays, indicating the importance of the selection of metal core and structure of metal complex for antiviral activity. Safe, effective, and preferably oral at-home therapeutics for COVID-19 are needed and as such zinc pyrithione, which is also commercially available, could be considered as a potential therapeutic agent against SARS-CoV-2.